Jaringan dan Sistem Sosial dalam Distribusi Komoditas Pertanian Lahan Kering - Fadly Husain; Gunawan Gunawan; Thriwaty Arsal; Asma Luthfi; Hartati Sulistyo Rini (JSW (Jurnal Sosiologi Walisongo), 2018)
Farming systems in the highlands have special typologies, as the development of dryland farming systems in the form of “tegalan” or gardens. This farming system also exists in several regions in Central Java. The aim of the study is to understand the distribution network system of local commodities (coffee, cocoa, and sugar palm at the local level). This study used qualitative research methods. The subjects in this study were the community (farmers) in Medono Village, Boja District, Kendal Regency. The results showed that the coffee and palm sugar distribution network system is carried out by collectors who come from local people and vendors or entrepreneurs from outside the village.